THE PRESENCE OF VOID IN HÉLIO OITICICA'S PROPOSITIONS - Hipólito, Rodrigo (Revista do Colóquio, 2025)
This paper addresses the confluence of spectator-work-author in Neoconcrete art, analyzing the propositions of Hélio Oiticica. Through the lens of Merleau-Ponty's negativist philosophy and Ferreira Gullar's "non-object," the position of the phenomenal subject as a generator of intuitive knowledge in the experience with Oiticica's propositions is highlighted.